FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Jasa yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Mutia Triyaningtyas; Sudarno Sudarno (Diponegoro Journal of Accounting, 2019)
One of the qualitative characteristics of attribute of financial statement reporting is relevant, that can be seen from the timeliness of reporting. Timeliness could be judging from the audit report lag, which is the different of the financial statement date to the date of the auditor’s opinion on the financial statements. The reason that makes researcher interest in this field is that audit process can cause report lag in reporting of financial statement. The research design used in this study is a replication from previous study conducted by Baldacchino et al. (2016) about an analysis of audit report lags in Maltese companies. The purpose of this research is to examine the impact of company size, public accountants firm size, and audit opinion toward audit report lag in service company sector that listed on Indonesia Stock Exchange.The population in this study consists of service companies that listed on Indonesia Stock Exchange for 2012 till 2015. Sampling method that used is purposive sampling. The samples consist of 96 financial statements from 24 service companies. Data used in this research is audited financial statements from each company that have been published. Multiple regression is used to be an analysis technique by SPSS version 22.The empirical result of this study show that public accountants firm size, and audit opinion have significant influenced on audit report lag. Company size has no significant influence to audit report lag